2022
DOI: 10.3389/fimmu.2022.956224
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analyses and molecular subtypes based on the cancer-associated fibroblast landscape and tumor microenvironment infiltration characterization reveal clinical outcome and immunotherapy response in epithelial ovarian cancer

Abstract: BackgroundCancer-associated fibroblasts (CAFs) are essential components of the tumor microenvironment (TME). These cells play a supportive role throughout cancer progression. Their ability to modulate the immune system has also been noted. However, there has been limited investigation of CAFs in the TME of epithelial ovarian cancer (EOC).MethodsWe comprehensively evaluated the CAF landscape and its association with gene alterations, clinical features, prognostic value, and immune cell infiltration at the pan-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Moreover, the stromal cells were ranked according to three distinct CAF scores 3638 and robustly showed that both CM-CAFs and OC-CAFs significantly ranked higher for CAF scores than HUFs (Figure 4D). Similarly, considering the clear implication of CAFs in ECM remodeling, three ECM scores were produced 39,40 , and again both CM-CAFs and OC-CAFs significantly ranked higher for ECM scores than HUFs (Figure 4E).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the stromal cells were ranked according to three distinct CAF scores 3638 and robustly showed that both CM-CAFs and OC-CAFs significantly ranked higher for CAF scores than HUFs (Figure 4D). Similarly, considering the clear implication of CAFs in ECM remodeling, three ECM scores were produced 39,40 , and again both CM-CAFs and OC-CAFs significantly ranked higher for ECM scores than HUFs (Figure 4E).…”
Section: Resultsmentioning
confidence: 90%
“…All volcano plots were built using the EnhancedVolcano R package and all heatmaps were built using the ComplexHeatmap R package. Using the RNA-sequencing results for HUFs, CM-CAFs, and OC-CAFs with the GSVA R package, an ECM score was produced using three gene sets from the GSEA website for the core, associated, and complete Naba matrisome and a CAF score was produced from gene sets used in previous studies: 24 carcinoma-associated fibroblast genes upregulated by MSCs grown in tumor conditioned media 37 ; 7 CAF markers used to identify two CAF subtypes 36 ; and 5 CAF markers used to identify four CAF subtypes 38 . A dataset of OC patients from Tothill et al 35 was obtained through accession GSE9899.…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 27, 2023. ; https://doi.org/10.1101/2023.02. 27.529938 doi: bioRxiv preprint α (FAP) 18 , that correlates with both poor prognosis and response to immunotherapies 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Together, these physical and chemical barriers foster T-cell exclusion and exhaustion 14, 15 . CAF-rich tumors are thus often ‘cold’ nonimmunogenic tumors with a T-cell deficient immune desert signature landscape 16, 17 Corroboratively, over 90% of epithelial cancers including breast, colorectal, pancreatic and lung adenocarcinomas express the CAF-specific surface marker, fibroblast activation protein-α (FAP) 18 , that correlates with both poor prognosis and response to immunotherapies 19, 20 . Fortunately, other than a small fraction of cells in the proliferative stage of placenta and uterine stroma, embryonic tissue and multipotent bone marrow stromal cells, FAP is not expressed in healthy adult tissues 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation